Physico-chemical analysis of kanakalinga karpurathy mezhugu – A Siddha herbo mineral compound - V. Elango; J.Jeya venkatesh (International Journal of Pharmacy and Analytical Research, 2022)
The present study is aimed at the characterization of the physico -chemical traits of the traditional Indian Siddha medicine, Kanakalinga karpurathy mezhugu. FT-IR spectroscopy has been used to study the presence of organic substance compound and complexes in the sample. Proton NMR studies help to characterize the structure of the functional groups in the sample. The study highlights the appropriate application of modern scientific methods for developing new insights into metal based siddha drugs.